Measuring the Effect of Consumer Protection Laws on Consumer Purchase Intention with Consumer’s Attitude toward Deception as a Mediator - ALQAYSI, Sahar Jalal; ZAHARI, Abdul Rahman (International Journal of Membrane Science and Technology, 2023)
Marketing deception in Iraq is different from other countries due to the absence of ?governmental control, corruption, the political composition and structure of the country. This study aims to test the effect of consumer protection laws on consumer purchase intention. The data were collected by a questionnaire distributed randomly to customers local Supermarkets in Erbil, Kurdistan Region of Iraq. A random sampling technique was used. Accordingly, 300 respondents participated in the survey, and 275 valid responses were received, demonstrating a 92% response rate. The hypothesis was tested by employing Partial least squares structural equation modelling (PLS-SEM). The finding showed consumer protection laws have significant effect on consumer purchase intention. Also, the relationship between consumer protection laws and consumer buying intention was mediated by consumer attitude. The outcomes propose that strong laws and regulation by the government favor both consumers and marketers and will increase the attitude of consumers toward purchasing a product.